Submission from the CGIAR System Organization, International Centre for Tropical Agriculture and the World Bank, in response to Decision 4/CP.23. - CGIAR System Organization; International Center for Tropical Agriculture; World Bank (2019)
Although there is increasing visibility and international frameworks for soil organic carbon, investment and action at sufficient scales is lagging behind. Practices that retain and increase soil organic carbon are well established but their effect is highly context specific. There is less understanding on pathways towards bringing the relevant practices to scale and investment has remained far below the necessary volume.